ESTIMACIÓN DE DENSIDAD DE FIBRA EN ALPACAS DEL CENTRO DE DESARROLLO ALPAQUERO TOCCRA CEDAT – DESCO DEL DEPARTAMENTO DE AREQUIPA: ESTIMACIÓN DE DENSIDAD DE FIBRA EN ALPACAS DEL CENTRO DE DESARROLLO ALPAQUERO TOCCRA CEDAT – DESCO DEL DEPARTAMENTO DE AREQUIPA - FLORES ALCA, VERONICA (2022)
The research was carried out at the Alpaquero Toccra CEDAT- DESCO Development Center, located in the Department of Arequipa; with the aim of quantifying fiber density (DenFib), density of hair ducts (DenCP) and fiber/duct ratio (Fib/CP), as well as estimating the degree of relationship between these characteristics. 344 alpacas of different ages and sex were evaluated. To quantify the indicated characteristics, the procedure and equipment called FIBER DEN was used. The evaluation in each animal was carried out in five places at the level of the middle rib, capturing images of 1mm2 area. Data were analyzed in a completely randomized design with a 4x2 factorial arrangement, using SAS version 9.4 software. To assess the relationships between fiber density and hair ducts, Pearson's correlation coefficient was determined. The means ± standard error (SE) for DenFib, DenCP and Fib/CP obtained were 24.75±0.30 fibers/mm2 7.83±0.12 hair canals/mm2 and 3.25±0.03 fibers per hair canal, being affected by age and sex DenFib, DenCP but Fib/CP is only affected by age. The correlation between fiber density and hair canal density was positive and moderately high (r=0.78) but between DenCP and Fib/CP it was negative (r=-0.56). It is concluded that DenFib and DenCP decrease with age and that males have higher DenFib and DenCP, with a strong direct relationship between them, but an inverse relationship between DenCP and Fib/CP.